Prospects and Challenges of Green Sukuk for Sustainable Development Projects in Malaysia - Sulaiman, Ahmad Azam; Mohamad, Mohammad Taqiuddin; Mustapa, Siti Salwani (ISLAMICONOMIC: Jurnal Ekonomi Islam, 2023)
The issuance of green Sukuk in mid-2017 has become an increasingly attractive mechanism for investors and issuers to increase the capital of projects, assets or other activities that benefit the economy, environment and whole of society. The main objective of this study is to examine the current status of green Sukuk since it was published from July 2017 to March 2018 as well as review the prospects and challenges of green Sukuk in Malaysia. This study critically examines the various literature, aimed at emphasizing possible opportunities for future success and challenges to investors in investing in green Sukuk. The results of this study show that the possibilities and opportunities of green Sukuk in the future through various prospects can have a positive impact to encourage the growth of green Sukuk. In the fast-growing capital market in Malaysia, challenges are inevitable and may arise when organizations assess whether issuing green Sukuk is the right course of action. The findings of this study provide useful information to individual investors, investment companies and implemental companies to identify prospects and challenges in implementing green Sukuk so that the preparation and improvement in complying with sharia law can be done, achieve the purpose of environmentally friendly investment as well as generate good profits.